2013
DOI: 10.1095/biolreprod.113.108167
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Vitrification on the Meiotic Spindle and Components of the Microtubule-Organizing Center in Mouse Mature Oocytes1

Abstract: Cryopreservation of oocytes is becoming a valuable method for fertility preservation in women. However, various unphysiological alterations occur in the oocyte during the course of cryopreservation, one of which is the disappearance of the meiotic spindle. Fortunately, the meiotic spindle does regenerate after thawing the frozen oocytes, which enables completion of meiosis and further development after fertilization. Nonetheless, the mechanistic understanding of the meiotic spindle regeneration after cryoprese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 54 publications
0
36
0
2
Order By: Relevance
“…In agreement with our study, it has been reported that the vitrified/warmed GV stage oocytes in ovine and other species have lower potential to reach MII stage compared with non‐vitrified oocytes (Moawad et al, ). Cryopreservation can disrupt the normal functions of the oocyte, such as re‐initiation and completion of meiosis, reorganization of cytoplasmic components during maturation, fertilization and the subsequent embryo development (Tamura, Huang, & Marikawa, ). Therefore, in our study, the reduction of nuclear maturation in vitrified/warmed oocytes might be one of the reasons for decreasing the developmental competence of these oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with our study, it has been reported that the vitrified/warmed GV stage oocytes in ovine and other species have lower potential to reach MII stage compared with non‐vitrified oocytes (Moawad et al, ). Cryopreservation can disrupt the normal functions of the oocyte, such as re‐initiation and completion of meiosis, reorganization of cytoplasmic components during maturation, fertilization and the subsequent embryo development (Tamura, Huang, & Marikawa, ). Therefore, in our study, the reduction of nuclear maturation in vitrified/warmed oocytes might be one of the reasons for decreasing the developmental competence of these oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been observed that while the freezing procedure takes place, the spindle configuration may be preserved if oocytes are exposed to cryoprotectants, its structure is completely lost during the thawing procedure . However, further evidence has highlighted a recovery ability of the spindle to reassemble following cryopreservation . This de novo reassembly of the spindle microtubules is a requirement for correct chromosome alignment and segregation after fertilization .…”
Section: Factors Influencing Oocyte Cryopreservationmentioning
confidence: 99%
“…The goal of vitrification is to minimize IIF and dehydration (or freeze concentration) altogether, but the conventional procedure of vitrification requires a high concentration of CPAs (up to ~8 M, high-CPA) that may induce significant osmotic and metabolic damage to cells including oocytes even in a short exposure of a few minutes [11,36,40]. For example, a high concentration of CPA has been shown to induce cytoskeletal alternations [5,35], dispersal of chromosome [30], and disassembly of spindles [32] in oocytes. Consequently, it is necessary to use multiple steps to gradually load and unload the high CPA to minimize osmotic and metabolic damage to cells during high-CPA vitrification, making it a complicated, lengthy, and stressful process [12,13,29].…”
Section: Introductionmentioning
confidence: 99%